Mindfulness‐based stress reduction for mental health in youth: a cluster randomized controlled trial. Issue 1 (15th October 2018) - Vohra, Sunita; Punja, Salima; Sibinga, Erica; Baydala, Lola; Wikman, Erik; Singhal, Anthony; Dolcos, Florin; Van Vliet, K. Jessica
Abstract : Background: Mental illness is among the most common causes of morbidity, mortality, and disability in childhood. Mindfulness‐based stress reduction (MBSR) has shown significant benefit in mental health; however, evidence of its effectiveness in youth is limited. The objective of this study was to compare the efficacy of MBSR plus usual care versus usual care alone for reducing mental health symptoms in youth. Methods: A two‐arm, mixed methods, randomized cluster‐controlled trial of 12–18 year olds who were residents of CASA House, a voluntary residential treatment program for adolescents, between January 2011 and March 2013 (clinicaltrials.gov, NCT01307943). Interventions: Treatment terms were randomized to usual care, or MBSR plus usual care, which included eight MBSR sessions of 2 hr/week. Outcomes: The primary outcome was impact on emotions and behavior at the end of the program, using the Behavior Assessment System for Children, Second Edition (BASC‐2). Secondary outcomes included perceived stress levels, mindfulness, and emotional regulation. Results: A total of 85 participants were randomized to either the MBSR arm ( n  = 45) or control arm ( n  = 40). Significant differences in favor of MBSR were found on Teacher ratings of the Internalizing Problems ( p  = .038) and Adaptive Skills subscales ( p  = .022) on the BASC‐2. No significant differences were found on other outcomes. A post hoc analysis found that the MBSR arm had a significantly shorter time to discharge ( p  = .02). Conclusion: The results of this study indicate that MBSR is effective for improved coping with internalizing problems and adaptive emotional skills in our sample. Future studies should focus on larger, longer‐term studies in youth.